Growth and feed efficiency of growing dairy replacement heifers supplemented with Rumensin or Bovatec - Michael V. Scheffel; A. Park; John F. Smith; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 1998)
Ninety Holstein heifers were used to examine the effects of Rumensin® or Bovatec®. Average daily gain and feed efficiency was greater for heifers fed Rumensin® than for heifers fed Bovatec®. Heifers fed Rumensin® consumed more total dry matter per day but slightly less dry matter as a percent of body weight than heifers fed Bovatec®. No differences were observed in body condition score and hip height between dietary treatments. The primary goal of a heifer-feeding program is to obtain a desired rate of gain without fattening at the least possible cost. Results of this study support the use of Rumensin® in diets for growing dairy replacement heifers.; Dairy Day, 1998, Kansas State University, Manhattan, KS, 1998;
Keywords: Dairy Day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-158-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 821; Replacement heifers; Rumensin; Bovatec